Faktor-faktor yang Mempengaruhi Nilai Arus Puncak Batuk pada Dewasa Muda Sehat Indonesia (Mongoloid) - Nusdwinuringtyas, Nury; Fauzan, Adri; Rumende, C Martin (Majalah Kedokteran Indonesia, 2019)
Introduction: Cough is one of the main human defense mechanisms against respiratory tract infection and aspiration. Until now, there has not been any Peak Cough Flow (PCF) standard value in Indonesia. The preexisting standard PCF values were measured in Brazil (2012) and New Zealand (Caucasian). There were anthropometric differences based on race, which affect PCF. The aim of this study is to determine the PCF of healthy Indonesian adults and affecting factors.Methods: This study used crossectional in design. A number of 30 healthy adult subjects were recruited and analyzed. Chi-Square and multivariate analyses. Screening subjects was measured using spirometry test and cough ability using peak flow meter.Results: The mean PCF was 477.17 (L/min). There was significant correlation between gender (p=0.000), age (p=0.012;r=-0.430), and height (p=0.000;r=0.741) to PCF. Height was the most contributing variable (p=0.003;IK95% 2.37-10.77).Conclusion: The mean PCF in healthy adults was 477.17(L/min). Height was the most contributing factor, followed by age and gender.